2005
DOI: 10.1002/acp.1163
|View full text |Cite
|
Sign up to set email alerts
|

Expertise and recollective experience: recognition memory for familiar and unfamiliar academic subjects

Abstract: Two experiments investigated whether expertise effects in recognition memory could be found for different academic subjects. The roles of subjective experience and repetition on such effects were also explored. Experiment 1 showed that overall recognition memory was greater for familiar than for unfamiliar academic words (the expertise effect). Additionally, this effect was attributable to the subjective experience of remembering rather than knowing. Experiment 2 showed that repetition of stimulus items at stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
8
30
0
Order By: Relevance
“…Participants with higher levels of car expertise (i.e., car experts) recognized cars more accurately and "recollected" old cars more often than participants with lower levels of expertise (i.e., car novices), 2 as observed frequently in previous research (Brandt et al, 2005;Goldin, 1979;Kawamura et al, 2007;Long & Prat, 2002;Rawson & Van Overschelde, 2008). Effect sizes of the expertise effects in our study were small to medium, replicating previously reported effect sizes in memory performance for experts and novices (Horry et al, 2010;Long & Prat, 2002;Marcon et al, 2009).…”
Section: Behavioral Memory Performancesupporting
confidence: 88%
See 4 more Smart Citations
“…Participants with higher levels of car expertise (i.e., car experts) recognized cars more accurately and "recollected" old cars more often than participants with lower levels of expertise (i.e., car novices), 2 as observed frequently in previous research (Brandt et al, 2005;Goldin, 1979;Kawamura et al, 2007;Long & Prat, 2002;Rawson & Van Overschelde, 2008). Effect sizes of the expertise effects in our study were small to medium, replicating previously reported effect sizes in memory performance for experts and novices (Horry et al, 2010;Long & Prat, 2002;Marcon et al, 2009).…”
Section: Behavioral Memory Performancesupporting
confidence: 88%
“…Only experts possess this ability as indicated by better subordinate categorization ability and lower false alarm rates. They are thus more likely not only to encode quantitatively more representations, but also to create qualitatively different -more distinct and detailed-representations that emphasize those features that facilitate within-category discrimination (Brandt et al, 2005;Goldstone, 1998). Our results confirm this assumption.…”
Section: Erp Retrieval Effectssupporting
confidence: 80%
See 3 more Smart Citations